1999
DOI: 10.1002/(sici)1097-0274(199906)35:6<574::aid-ajim4>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Zinc exposure in Chinese foundry workers

Abstract: Background: Inhalational exposure to zinc oxide fumes is associated with metal fume fever, a self‐limited but very uncomfortable condition closely resembling influenza. Very little is known regarding the toxicokinetics of inhaled zinc, making the interpretation of zinc measurements in serum and urine problematic. Methods: Twenty workers in a zinc foundry in Baiyin, Peoples' Republic of China, were investigated with serial examinations by a physician, chest radiographs, and spirometry. Exposure assessment consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 13 publications
7
43
1
1
Order By: Relevance
“…did not provide estimates of the relationship between zinc exposure levels and the levels of zinc in biological fluids but collectively confirmed that zinc was absorbed following inhalation exposure [14,[29][30][31]. However this data should be interpreted cautiously for several reasons.…”
Section: Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…did not provide estimates of the relationship between zinc exposure levels and the levels of zinc in biological fluids but collectively confirmed that zinc was absorbed following inhalation exposure [14,[29][30][31]. However this data should be interpreted cautiously for several reasons.…”
Section: Investigationsmentioning
confidence: 99%
“…As the composition of the plating bath depends on the processes Primary pulmonary involvement is characterized by reduced lung volumes and a decreased diffusing capacity of carbon monoxide [11][12][13]. Signs/symptoms usually occur within 4-8 h after exposure to Zn/ZnO fumes and persist for h. An increased tolerance develops within repeated exposures but it is lost after a brief period without exposure: as MFF symptoms are most commonly reported at the beginning of the working week and after holidays, it is otherwise called "Monday morning syndrome" [14]. Zinc exposure in the general population occurs primarily through ingestion, with an average intake of 5.2-16.2 mg/day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This heating results in the formation of fresh zinc oxide particles (0.2-1.0 µm), which may subsequently be inhaled. Inhalation of zinc oxide particles and fumes by workers can result in metal fume fever (Martin et al 1999). Inhalation was reported to be the most probable route of exposure to zinc for 26 lead smelter workers found to have significantly (p<0.01) elevated blood plasma levels of zinc.…”
Section: General Population and Occupational Exposurementioning
confidence: 99%
“…Mean plasma zinc concentrations were 12.9 mmol/L (range, 9.8-16.7) for the workers versus 10.9 mmol/L (range, 8.1-14.6) for a nonlead-exposed control group (Vasikaran et al 1992). Twenty workers in a zinc foundry in Baiyin, China were investigated for exposure to zinc oxide fumes (Martin et al 1999). Eighteen of the workers had worked at the foundry since its opening 6 years earlier.…”
Section: General Population and Occupational Exposurementioning
confidence: 99%